2012
DOI: 10.1258/jrsm.2012.120044
|View full text |Cite|
|
Sign up to set email alerts
|

Rethinking WHO guidance: review of evidence for misoprostol use in the prevention of postpartum haemorrhage

Abstract: SUMMARYThis article describes and critically appraises clinical trials assessing misoprostol effectiveness in preventing primary postpartum haemorrhage (PPH) in home and community settings in low-and middle-income countries. Of 172 identified studies of misoprostol use in labour only six fulfilled the inclusion criteria. All trials used 600μg misoprostol in the intervention arm; three assessed misoprostol alongside components of active management of the third-stage labour (AMTSL), two used expectant management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Even after the WHO’s decision to support misoprostol use for PPH prevention at home births, there have been continued opponents of misoprostol use for this purpose, claiming insufficient evidence [43]. Other researchers pooled existing study data to determine the potential impact of misoprostol on PPH mortality and found that its use neither increased nor decreased mortality or severe morbidity [44].…”
Section: Resultsmentioning
confidence: 99%
“…Even after the WHO’s decision to support misoprostol use for PPH prevention at home births, there have been continued opponents of misoprostol use for this purpose, claiming insufficient evidence [43]. Other researchers pooled existing study data to determine the potential impact of misoprostol on PPH mortality and found that its use neither increased nor decreased mortality or severe morbidity [44].…”
Section: Resultsmentioning
confidence: 99%
“…This body of evidence led the World Health Organization (WHO) to amend its model list of essential medicines in March 2011 to include misoprostol for the prevention of PPH in settings “where oxytocin is not available or cannot be safely used” [20], although some have expressed concern about this decision [21]. …”
Section: Introductionmentioning
confidence: 99%
“…55-57 This is the first study that has systematically evaluated the use of misoprostol for reducing intraoperative and postoperative blood loss in women undergoing cesarean delivery. The pooled evidence in our systematic review shows that, overall, the combined use of misoprostol and oxytocin appears to be more effective than oxytocin alone in reducing intraoperative and postoperative hemorrhage at cesarean delivery.…”
Section: Commentmentioning
confidence: 99%